Description of Pseudacrobeles (Bunobus) arboricola sp. n.(Rhabditida: Cephalobidae) from rotting wood in Roztochya, Ukraine (Journal of Nematode Morphology and Systematics, 2010)
Pseudacrobeles (Bunobus) arboricola sp. n., a new species of free-living nematodes from rotting wood in Ukraineis described. It is characterised by the absence of labial and cephalic probolae, presence of bar-shaped cheilorhabdia, low corpus-isthmus ratio (1.5-2.3), excretory pore anterior to corpus-isthmus junction, spermatheca 48-85 μm long, posterioruterine branch 10-22 μm long, rectum 25-31 μm long, ventrally curved elongate-conoid female tail (c’=4.9-6.8) with acute terminus, and short and ventrally curved conical male tail (c’=2.8-3.6) with rounded terminus bearing a short acute mucro.It differs from all hitherto described species of Pseudacrobeles (Bunobus) by the very anterior position of excretory pore and in the combination of characters listed above.